The observation of anterior segment in children with an R124L mutation corneal dystrophy by anterior segment optical coherence tomography and in vivo confocal microscopy - Fu, Mengjun; Zhao, Jing; Zhang, Haorun; Wang, Rui; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To evaluate the anterior segment in children with corneal dystrophy (CD) and R124L mutations using optical coherence tomography (OCT) and confocal microscopy. Methods: We investigated a family with prevalent CD and an R124L mutation; 59 individuals (14 patients; six male and eight female, aged 2-69 years, six children, 2:4 male: female ratio) from four generations were included. We observed corneal lesions through ophthalmologic examinations, OCT, and confocal microscopy. The mean follow-up was 4.60±3.91 years. Results: The mean age for childhood CD onset was 0.90±0.61 years. An Avelino DNA test revealed a heterozygous R124L mutation. Clinical manifestations included recurrent photophobia, tearing, and a foreign body sensation. Recurrence frequency decreased with age. Slit lamp microscopy revealed a rough corneal epithelium. The anterior matrix under the corneal epithelium and the anterior elastic layer were scattered with gray and white opacity. From onset to follow-up, the children’s visual acuity decreased from 0.34±0.12 to 0.55±0.17 LogMAR units. OCT showed uneven corneal epithelial thickness. The Bowman’s layer was replaced by abnormal substances in the anterior segment. Corneal deposits became increasingly thicker; the average thickness at the last follow-up was 102.78±10.13 μm. Confocal microscopy revealed uneven and reflective signals in the corneal upper cortex and subepithelium, with unclear boundaries and a loss of normal cell morphology. Conclusions: We report an early age of onset in a family with prevalent CD due to R124L mutations. Anterior OCT is a convenient, quick, and non-contact tool for screening and monitoring the pathological process of corneal dystrophy.